Little fires everywhere - Ng, Celeste (Penguin Press, 2017)
When a custody battle divides her placid town, straitlaced family woman Elena Richardson finds herself pitted against her enigmatic tenant and becomes obsessed with exposing her past, only to trigger devastating consequences for both families.